2023
DOI: 10.1002/cctc.202201514
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Electrochemical Promotion of Cu/Co3O4 Catalysts for the Reverse Water Gas Shift Reaction

Abstract: In this study, Copper-modified Co 3 O 4 (Cu/Co 3 O 4 ) catalysts were investigated for the reverse water gas shift (RWGS) reaction at 200-400 °C under different CO 2 : H 2 ratios. It was found that the electrocatalytic performance of Co 3 O 4 was improved by loading 4 weight percent (wt.%) Cu nanoparticles (average size: 13 nm), which could be then used as an electrode in electrochemical promotion of catalysis (EPOC) studies. Under the applied voltages of + 2 V and À 1 V, the catalytic rates were suppressed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Despite the formation of Cu 2+ , Cu 0 and Cu 1+ were still the main phases after the reactions due to the protection of ZnO support. The XPS spectra of O 1s for as-prepared ZnO, 10CuZnO, and 60CuZnO are compared in Figure c, with lattice O 2– (O L , represents Zn–O bonding) of ZnO found at 530 eV, defect O 2– (O V , represents oxygen-deficient region) of ZnO observed at 531 eV, and adsorbed oxygen (−OH) located at 532 eV. , It was found that by increasing Cu content from 0 to 60 wt %, the O L increased from 44.19 to 64.23% and the O V decreased from 48.58 to 21.47%. Moreover, the O L peak position shifted from 530.25 to 530.8 eV.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the formation of Cu 2+ , Cu 0 and Cu 1+ were still the main phases after the reactions due to the protection of ZnO support. The XPS spectra of O 1s for as-prepared ZnO, 10CuZnO, and 60CuZnO are compared in Figure c, with lattice O 2– (O L , represents Zn–O bonding) of ZnO found at 530 eV, defect O 2– (O V , represents oxygen-deficient region) of ZnO observed at 531 eV, and adsorbed oxygen (−OH) located at 532 eV. , It was found that by increasing Cu content from 0 to 60 wt %, the O L increased from 44.19 to 64.23% and the O V decreased from 48.58 to 21.47%. Moreover, the O L peak position shifted from 530.25 to 530.8 eV.…”
Section: Results and Discussionmentioning
confidence: 99%
“…CV is commonly applied to the catalyst-working electrode to investigate the redox properties of materials and provide in situ information about the electrochemical processes and changes in the oxidation states, and thus is widely used in EPOC studies as an electrochemical characterization method. ,, Figure a,b shows the CVs of as-prepared Cu/ZnO catalysts deposited on YSZ in argon at 400 °C. The CVs cycled from −0.8 to 1.5 V and then back to −0.8 V at a scan rate of 20 mV s –1 , where the anodic cycle involved electro-oxidation and the cathodic cycle involved electro-reduction.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation